Les nouveaux réalistes : Un manifeste de la nouvelle peinture - Restany, Pierre; Ragon, Michel (Paris : Editions Planète, 1968)
Duchamp, Marcel ; Schwitters ; Bruyen, Camille ; Klein, Yves ; Tinguely ; Christo ; Dufrêne ; Deschamps ; De Saint-Phalle, Niki ; Villéglé ; Spoerri ; Arman ; Rotella ; Hains, Raymond ; Raysse, Martial ; César ; etc.
Frans
boek